Terapi Dan Pola Hidup Sehat Pasien Hipertensi Untuk Menuju Gerakan Masyarakat Hidup Sehat - Fandinata, Selly Septi; Putra, Deddy Aryanda (Indonesian Journal of Community Dedication in Health (IJCDH), 2021)
Hypertension is a disease that occurs due to increased blood pressure. GERMAS and healthy family program through a family approach. The purpose of this community service activity is to provide counseling and know community knowledge about treatment therapies and healthy lifestyles, especially about the management hypertension therapy in Keboan Sikep Village, Gedangan Sidoarjo. The implementation method is by counseling, pre-post questionnaire and checking blood pressure and blood sugar level of participants. The results of this community service got 43 participants with a high blood pressure profile of 32 participants (74.42%), normal as many as 11 participants (25.58%) and none were classified as low. The profile of random blood sugar levels was classified as high as 6 participants (13.95%), normal as many as 36 participants (83.72%) and as low as 1 participant (2.33%). The results of the pre-test and post-test questionnaire showed that 28 participants (65.12%) (pre-test) had high adherence increased by 41 participants (95.35%) (post-test), and low adherence of 15 participants (34.88%) (pre-test) decreased by 2 participants ( 4.65%) (post test) this shows that an increase in the level of knowledge after the provision of health education.